E hoa ma, ina te ora o te tangata (My friends, this is the essence of life): Meal-making as a pedagogical tool for learning about food politics. Issue 7 (October 2019) - Kiddle, Rebecca; Mawer, Chantal; McAuliffe Bickerton, Ceara; Ryan, Alyssa; Siemonek, Laurette
Many environmental concerns such as climate change and reducing fossil-fuel dependence seem 'out of reach' for the majority of us regarding creating change. However, food systems and how we interact with them, offer tangible opportunities to respond to these environmental concerns in small but meaningful ways. By examining the impact of our food consumption, we are provided with an opportunity for ongoing self-assessment. To engage in this self-assessment as part of a community of practice, we argue, is all the more impactful. This paper is self-reflective, exploring the process and outcomes of a group of non-experts working together to develop a workshop to explore the politics of everyday eating. This workshop took the form of a seven-course meal. To disquiet this indulgence, these seven courses included both food for physical sustenance and food to provoke hearts and minds, because 'we don't usually think of what we eat as a matter of ethics' (Singer and Mason, 2007 : 3). The three food courses were sourced and cooked for conference participants by the authors of this paper. While undertaking these activities, we debated and documented our sourcing decisions and mused on the role of food in Aotearoa New Zealand. The remaining four courses served our guests the critical musings of food rescuers, local food producers and other food thinkers to cleanse the palate by way of presentations, poetry and performances. By using a meal as our methodology, we, as non-expert organizers and chefs, sought to explore our own, and allow others to explore their food consumption and ethics.